Questions on Cost-Benefit Analysis and a Discussion of Present Answers: How Should One Determine the Social Discount Rate to Be Announced? - Guesnerie, Roger; Maurice, Joël (Journal of Applied Business and Economics, 2023)
In the wake of the CBA used for public investment programming in France, new recommendations have been formulated for projects whose advantages (costs or benefits) are exposed to macroeconomic risks (correlation with GDP per capita), distinguishing between classically Gaussian hazards and “rare disasters” à la Barro. Taking rare disasters into account significantly modifies the value of the discount rate, along with the mathematical expectation of the advantages, and accentuates the distinction between procyclical and counter-cyclical projects.